Methods of hedging against exchange risk exposure. The example of exchange risk management in Klockner Chemia Polska Sp. z o.o. - Pazera Ewa (My University, 2001)
The thesis is devoted to exchange rate risk and its management on the basis of the example of Klöckner Chemia Polska Sp. z o.o. It discusses the problems the company faced in 1998 when the crisis connected with devaluation of Russian currency took place. The dissertation shows the means KCP could have used to prevent losses. The background of international trade is presented, the risks connected with international trading, especially the exchange rate risks (operating, accounting and transaction risks) are discussed and some methods of hedging these risks are introduced. The exchange rate risk in the company, methods of its identifying, managing and limiting are discussed and some possibilities of natural and contractual hedging are presented. The description of the company and its activity the exchange risk it is exposed to and methods of hedging that risk used by KCP are analysed.
Keywords: international trade; exchange rate risk; hedging; swaps; futures contracts; exchange rate risk amnagement; finance